Optimal level of Bacillus spp. fermented soybean meal utilization in broiler diets under commercial conditions: effect on gut morphology and microbiota - Arif Martien Putra; Ma’ruf Tafsin; Nevy Diana Hanafi; Winda Fransisca Saragih; Yusni Khairani Tampubolon (Talenta Publisher, 2026)
Fermented soybean meal (FSM) using Bacillus spp. has the potential to be used as a functional feed ingredient to improve the intestinal health of broiler chickens, but the optimal level of use in feed in the commercial broiler industry has not yet been determined. A total of 20.000 cobb 500 broilers were allotted to four dietary treatments: control (T0) and rations containing 1.5% (T1), 2.5% (T2), and 5.0% (T3) FSBM, each with five replications. The chickens were reared under commercial industry conditions. Over a 28-day period, parameters measured included Growth performance indicators, small intestine histomorphometry, microbial populations, catalase and motility activity, and lactic acid bacteria counts. FSBM supplementation had no significant (P>0.05) effect on performance (feed intake, body weight gain, feed change ratio). However, T2 significantly increased basal and apical pH in the jejunum (P<0.05), along with elevated LAB counts and reduced intestinal pH, compared to the control. In conclusion, fermentation with Bacillus spp. represents an effective strategy to reduce anti-nutritional factors and enhance feed quality. The improved intestinal morphology and lactic acid bacteria populations in broilers observed in this study suggest that 2.5% FSBM. Therefore, Bacillus spp. fermented soybean meal has potential as a functional feed ingredient for commercial broiler production.